Desenvolvimento de um hidrogel à base de celulose contendo óleo essencial de melaleuca no tratamento de onicomicose causada por dermatófito e levedura - Destro, Thais Viço (2025)
Onychomycosis is an infection caused by non-dermatophyte fungi and yeasts and tinea unguium caused by dermatophytes, which affects 20% of the world's population and constitutes 50% of all nail diseases.Currently, innovative alternative therapies in the treatment of onychomycosis under investigation include the use of essential oils (EO) as possible antifungal agents.The objective of this research is to develop an innovative polymeric film with Hydroxypropylmethylcellulose (HPMC) and chitosan, associated with Melaleuca essential oil to form an adhesive film, following the solvent evaporation method. The following parameters will be evaluated: controlled release profile, zeta potential, FTIR, microbiological analysis and antifungigram test with Candida albicans yeast strains and Trichophyton rubrum fungus.Thermal, TG and DSC analyzes were analyzed and obtained the following results with: HPMC or HPMC+chitosan or HPMC+chitosan+melaleuca (1 and 2%) did not demonstrate changes that differ from the literature, therefore they presented thermal stability in all combinations. As a future expectation, it is expected that this film promotes effective release of the bioactive, adhesiveness, prolonged action time, reduction of the need for reapplication, and proof of antifungal activity against onychomycosis caused by Candida albicans and Trichophyton rubrum